Occupational restructuring in US high-tech manufacturing: 1983-1995. (1st January 2003) - Jr, Bill Luker; Lyons, Donald
We survey occupation-by-industry panel data from 1983 to 1995, documenting major changes in the occupational structure of employment in US high-tech manufacturing industries. On the non-production side, defence spending cutbacks, technical change and production strategies chosen in response to technical change are causing better-paid computer professionals and more senior executives to displace specialised computer technicians, administrative and managerial support workers and single-discipline engineers. On the production side, the same factors converge, creating the inverse of that trend: less well-trained and therefore less well-paid workers are replacing the more skilled. Although production-side down-skilling can sometimes be viewed as a relative up-skilling or re-skilling for operators and assemblers, these two main trends in high-tech occupational restructuring are exacerbating, rather than mitigating, growing wage and income inequality in the USA.